Corrosion behaviour of nanocomposite TiSiN coatings on steel substrates - Ahmed, M.; Munroe, P.; Jiang, Z.; Zhao, X.; Rickard, William; Zhou, Z.; Li, L.; Xie, Z. (Pergammon, 2011)
Nanocomposite TiSiN coatings were deposited on tool steels. Detailed mechanisms that govern the corrosion of these coated steels were revealed, following immersion tests in a 70% nitric acid solution. Pitting originated preferentially from coating defect sites and expanded with increasing immersion time. Both Young’s modulus and hardness measured by nanoindentation decreased as the corrosion damage intensified. A thin oxide layer formed from the thermal annealing of the as-deposited samples at 900 °C was found to be effective against corrosive attack. In addition, compressive residual stress was noted to suppress the propagation of corrosion-induced cracks. The role of residual stress in controlling the corrosion resistance of these ceramic-coated steels is clarified by finite element analysis.